Some aspects of teaching professional foreign language at physico-technical faculty (Eurasian Journal of Philology Science and Education, 2016)
At present, more and more scientific articles of Kazakhstani authors are published in scientific journals in English. This poses new challenges for teachers of English. The necessity to teach students the basis of academic language and translation comes to the foreground. The result depends on the level of knowledge of the English language, and in this paper we consider some common errors that occur when translating modal verbs, synonymous phrases and verbal nouns, which are widely used in scientific texts. The paper presents examples of the use of modal verbs in scientific texts, some problems of teaching translation of scientific texts in terms of improving the efficiency of the process, as well as some specific issues, such as descriptions of particular interpretation of research results, which are of interest not only for students, but also for inexperienced translators of technical literature.
Keywords: translation from Russian into English; modal verbs; verbal nouns.